Implementation of narcotics criminal law in Indonesia - Maria MT Manurung; Dzaki Jumayyil Pohan (AT-TAFAHUM: Journal of Law, 2023)
The problem of narcotics crime has become a problem for nations and nations in the world that is always discussed. Throughout the world, the problem of narcotics abuse has almost become a problem for nations. And narcotics abuse can certainly cause physical damage, mental health, emotions and attitudes in society. The problem of narcotics abuse has threatened society and the nation so that it has become an organized crime in the national and international scope. Based on this background, the author raised a scientific journal entitled "THE IMPLEMENTATION OF NARCOTICS CRIMINAL LAW IN INDONESIA". Regarding this scientific journal, the author explains the problem of how the application of criminal law regarding the regulation of narcotics crimes in Indonesia and how the criminal law system regarding the regulation of narcotics crimes in Indonesia. The research method in this scientific journal is carried out with a normative juridical approach, namely by analyzing the problem through a legal principle approach and referring to legal norms contained in statutory regulations. The data used in this scientific journal is secondary data.